The Comparative Dynamics of Private Governance: The case of the Bangladesh Ready-Made Garment Industry - Erin Leitheiser (Copenhagen Business School (CBS), 2019)
This study investigates how and why companies engage in private governance in varied ways and the implications thereof. It compares how companies – as `political actors' – engage in private governance differently, even if in response to the same institutional pressures. In doing so, it examines the interplay between context (structure) and choice (agency). Overall, it contributes to our understanding of why companies understand their political roles and responsibilities differently, and the implications of these differences for the private governance of sustainability issues. In doing so, it contributes to our understanding of the organization and dimensions of private governance, the logics of different models of private governance and their potential for addressing different types of sustainability challenges, and the powerful role of actors' agency in shaping the environments in which companies provide governance. To complete this task, the PhD thesis is based on a comprehensive comparative case study of two competing private governance initiatives that emerged in the aftermath of the 2013 collapse of the Rana Plaza complex in Bangladesh. The first was the Accord, a substantive and legally enforceable agreement governed equally by business and labor and allowed for NGO members (thereby constituting a multi-stakeholder initiative, MSI). It garnered more than 220+ members during its tenure, including all of the European brands. Some North American companies cited the Accord's legal provisions and inclusion of labor as intolerable, and therefore walked away and created their own competing initiative, the Alliance, a business-led initiative (BLI) which was softer and principle-based. Both organizations formed during the same period and in response to the same pressures, yet took vastly different approaches to the shared end goal of factory safety. Their membership divide down country (U.S. vs. EU) and configurational lines (MSI vs. BLI) make it a robust case from which to investigate the influence of different institutions and contexts on the resulting private governance choices.
hdl:10398/9728
Keywords: 650